2022
DOI: 10.18632/oncotarget.28207
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on [5 fluorouracil and epigallocatechin-3-gallate] complex activity on HT-29 cell death and its stability in gastrointestinal fluid

Abstract: Recently an enhancement of the sensitivity of colorectal cancer (CRC) cells by 5-fluorouracil (5FU) due to the concurrent treatment with epigallocatechin-3gallate (EGCG) has been found. In the present paper, to investigate on this aspect, adenocarcinoma cells HT29 were treated with 5FU, EGCG and an equimolar mixture of 5FU and EGCG ([5FU+EGCG]) and cell viability was determined. While 5FU exhibits a clear activity, EGCG alone does not express any activity. However by treating the cells with [5FU+EGCG] a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Moreover, EGCG effectively decreased the dose of DOX needed to reach cytotoxicity by mediating P-gp activity in the Caco-2 cell line [182]. Similarly, EGCG and 5-FU synergistic effects have been reported in other colon and CRC cell lines as well [183,184]. La et al carried out an in vitro and in vivo investigation and described how EGCG managed to enhance the sensitivity of colon cancer cells to 5-FU by inhibiting the GRP78/NF-κB/miR-155-5p/MDR1 pathway and by promoting 5-FU accumulation in cancer cells [185].…”
Section: Colorectal Cancermentioning
confidence: 59%
See 2 more Smart Citations
“…Moreover, EGCG effectively decreased the dose of DOX needed to reach cytotoxicity by mediating P-gp activity in the Caco-2 cell line [182]. Similarly, EGCG and 5-FU synergistic effects have been reported in other colon and CRC cell lines as well [183,184]. La et al carried out an in vitro and in vivo investigation and described how EGCG managed to enhance the sensitivity of colon cancer cells to 5-FU by inhibiting the GRP78/NF-κB/miR-155-5p/MDR1 pathway and by promoting 5-FU accumulation in cancer cells [185].…”
Section: Colorectal Cancermentioning
confidence: 59%
“…Polonio-Alcalá et al demonstrated that EGCG combination with either GEF or osimertinib (OSM) resulted in mostly additive effects [179], while another study described how EGCG overcame GEF resistance in NSCLC through inhibiting autophagy and enhancing cell death by inhibiting the Raf/MEK/ERK pathway [180] (Table 4, Figure 4). [175][176][177][178][179][180], colorectal [181][182][183][184][185][186][187], liver [188], gastric [189] and breast [190][191][192][193] cancer) and clinical (lung [194][195][196] and breast [197,198] colorectal [181][182][183][184][185][186][187], liver [188], gastric [189] and breast [190][191][192][193] cancer) and clinical (lung [194][195][196] and breast [197,…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when the compounds were associated, the cytotoxic effect was enhanced, with approximately 13% of the cells remaining viable. A thorough review of the literature in the field led to the selection of the concentrations of 5-FU used in this study [51][52][53]. A study conducted by Srimuangwong et al assessed the effects of 5-FU at doses between 5 and 25 µmol/L on HT-29 cells, and it was found that the concentration of 25 µmol/L resulted in a reduction in viability below 80% after 48 h [54].…”
Section: Discussionmentioning
confidence: 99%